Dance and politics: Moving beyond boundaries - Mills, Dana (Manchester University Press, 2017)
"Since ancient times and across cultures, dance has provided a powerful form of human expression. In this inspiring book, Dana Mills examines the political power of dance from a global perspective. Mills explores different dimensions of dance as a form of intervention into a politics more commonly articulated in words. She is interested in dance as a system of communication that allows its subjects to speak with their bodies and to create embodied spaces, drawing attention to the radically egalitarian nature of dance with its ability to transcend all boundaries of gender, race and sexual politics. The book is structured around a range of cross-cultural and comparative examples, from the work of Isadora Duncan and Martha Graham to gumboot dancers in South Africa and the One Billion Rising movement, which uses dance to protest against gendered violence. Each case study references powerful dance 'moments', providing links to YouTube clips to allow readers to experience dance directly as they read. The case studies are discussed within a conceptual framework drawing on Rancière's concept of dissensus and in the light of recent work on embodied politics by political theorists including Jodi Dean and Jane Bennett. Dance and politics is aimed at a dual audience of political theorists and students and scholars of dance and performance. It will also be of great interest to readers seeking to expand their thinking about politics, embodiment and activism."